Intravesical OnabotulinumtoxinA Injection for Overactive Bladder Patients with Frailty, Medical Comorbidities or Prior Lower Urinary Tract Surgery - Liao, Chun-Hou (Toxins (Basel), 2016)
Overactive bladder (OAB) symptoms increase with age and involve several comorbidities. OnabotulinumtoxinA (BoNT-A) intravesical injection is a treatment choice for patients who are intolerant of or refractory to antimuscarinics. However, the increased risk of urinary tract infection and elevated post-void residual (PVR) volume post-treatment require resolution. Male sex, baseline PVR > 100 mL, and comorbidities are independent risk factors of adverse events (AEs) such as acute urinary retention (AUR). Intravesical BoNT-A injection is safe and effective for OAB patients with frailty, medical comorbidities such as Parkinson’s disease (PD), chronic cerebrovascular accidents (CVA), dementia, or diabetes, or a history of prior lower urinary tract surgery (prostate or transvaginal sling surgery). Post-treatment, 60% of frail elderly patients had a PVR volume > 150 mL and 11% had AUR. Although intravesical BoNT-A injection is safe for PD patients, CVA patients had higher strain voiding rates. Diabetic patients were at increased risk of large PVR urine volume and general weakness post-treatment. Treatment results were similar between patients with and without a history of prostate or transvaginal sling surgery. Possible AEs and bladder management strategies should be conveyed to patients before treatment. Careful patient selection is important, and therapeutic safety and efficacy should be carefully balanced.